Influence of confinement by transverse reinforcement on the nonlinear behaviour of reinforced concrete structures - Ourabah, Adnane; Bouafia, Youcef; Iddir, Abdelkader; Kachi, Mohand Said (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Structural design and calculation are based on the behavior of concrete and steel separately, without taking into account the contribution of stirrups in concrete confinement. The influence of confinement in structural modeling can be used to better approximate real behavior. The purpose of this study is to develop and validate a non-linear model for the behavior of reinforced concrete structures, taking into account concrete confinement.Methods: A 3D finite element model is used to analyze framed structures. This model takes into account shear deformations. The cross-section of the beam is discretized into trapezoidal layers, while each layer is assumed to be uniaxially stressed. Non-linear constitutive laws are applied to the materials. For concrete confinement, the material’s ductility is considered using the relationships proposed by Bouafia et al. These models are implemented in a computer program. The software monitors the behavior of column-beam structures under variable loads until reaching their load-bearing capacity.Results: The results are compared with experiment results, focusing on maximum strength and deformability. The comparison shows very satisfactory results. In addition, the use of transverse reinforcement for concrete confinement significantly impacts the global behavior of reinforced concrete structures by influencing the contribution of ductility.Conclusion: The consideration of confinement in structures provides the best possible approach to the real behavior of structures. In contrast to existing calculation codes, concrete behavior laws do not take into account the contribution of confinement by transverse reinforcement.
Keywords: reinforcement; confinement; modelling; simulation; ductility; stirrups